Effects of connectivity on animal‐dispersed forest plant communities in agriculture‐dominated landscapes. (6th May 2018) - Mony, Cendrine; Abadie, Juliet; Gil‐Tena, Assu; Burel, Francoise; Ernoult, Aude
Abstract: Questions: How does connectivity affect animal‐dispersed plant assemblages in woodlots of agriculture‐dominated landscapes? Is this effect dependent on zoochorous dispersal modes? Location: Long‐Term Socio‐Ecological Research (LTSER) site of "Zone Atelier Armorique" (ca. 150 km 2 ), Brittany, western France. Methods: We sampled 26 small post‐agricultural woodlots embedded in an agricultural matrix (1–7 ha). We assessed the connectivity of each woodlot using habitat reachability metrics (i.e. Proportion of Total Potential Dispersal Flux in the Landscape) calculated along a range of dispersal distances from 100 to 1, 500 m. This metric was based on graph theory and was calculated as a function of landscape matrix permeability to animal movement (i.e. seed plant dispersal vectors). We analysed the composition of plant assemblages in the core and margins of woodlots. We calculated the proportion of species richness and cover of zoochorous species within these assemblages and for specific zoochorous modes (i.e. epi‐, endo‐ and dys‐zoochorous species). We analysed the effects of Proportion of Total Potential Dispersal Flux at different dispersal distances and woodlot sizes on the functional dispersal structure of the plant community using linear models. Results: We demonstrated that overall plant zoochorous assemblages only depend on woodlot size in the range of dispersal distances tested. The proportion of richness of zoochorous species within the community increased with habitat size. Connectivity influenced only the relative proportions of the different zoochorous modes, except for the dys‐zoochorous group, which was primarily influenced by woodlot size. Both epi‐zoochorous and endo‐zoochorous species were impacted by the interaction between connectivity and woodlot area. Connectivity increased the proportion of epi‐zoochorous species richness and the proportion of endo‐zoochorous cover in assemblages in large woodlots. These effects were detected at short dispersal distances. Our results were supported in both total and core plant assemblages. Conclusion: This study indicates that both habitat isolation and decrease in habitat size contribute towards shaping the functional structure of the plant community, but they act at different levels of dispersal mode. Our results suggest that in these fragmented landscapes long‐distance dispersal has been lost either because of the selection of small‐sized animal movements or of the rareness of plant species needing large habitat size. Maintaining woodlot connectivity in the woodland surroundings seems to be sufficient to preserve short‐distance dispersal, although a more thorough restoration of landscape connectivity is necessary to recover the functional composition of the community with the whole set of dispersal patterns. Abstract : Both habitat isolation and decrease in habitat size shaped animal‐dispersed plant species assemblages in woodlots with varying effects depending on the dispersal modes. This work demonstrates that dispersal relies mostly on small‐distance mobility suggesting that long‐distance dispersal has been lost in these agricultural fragmented landscapes. It emphasizes the necessity of a thorough restoration of connectivity at the landscape level.